2019
DOI: 10.1016/j.afjem.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Boomslang bite in the Northern Cape

Abstract: Introduction The authors describe an atypical presentation after a Boomslang bite with rapid progression of symptoms and death. Case report A young gentleman was bitten and rapidly decompensated before monovalent antivenom could be administered, with fatal results. Conclusion This case highlights the importance of having monovalent Boomslang antivenom rapidly available in all referral centres that may be involved in the management of Boomslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…9 Once a patient deteriorates to clinical VICC, the consequences are life-threatening and costly. 4 The use of objective real-time whole blood coagulation studies like ROTEM/TEG can be helpful in the early diagnosis of lifethreatening bites. They may indicate the need for the early use of antivenom leading to an uncomplicated recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Once a patient deteriorates to clinical VICC, the consequences are life-threatening and costly. 4 The use of objective real-time whole blood coagulation studies like ROTEM/TEG can be helpful in the early diagnosis of lifethreatening bites. They may indicate the need for the early use of antivenom leading to an uncomplicated recovery.…”
Section: Discussionmentioning
confidence: 99%
“…If left unchecked, DIC ensues leading to death. 7 A number of case studies 4 , 8 have shown derangements of whole blood clotting time and standard coagulation tests (PT, PTT, INR and fibrinogen); however, there have been no direct comparisons of coagulation tests with VEA in the setting of boomslang bites. This emphasises the importance of this case report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Boomslangs ( Dispholidus typus ) have powerfully haemotoxic venom and are more frequently encountered within their range than potently neurotoxic black mambas ( Dendroaspis polylepis ) (e.g., 491 versus 127 iNaturalist records as of 28 June 2021). Generally shy and unobtrusive ( Marais, 2011 ) despite their broad distribution in sub-Saharan Africa only eight deaths due to Boomslang envenomation have been recorded since 1957 in South Africa ( Krüger and Lemke, 2019 ). Black mambas, with a similarly broad distribution, account for far more deaths from bites ( Ochola et al, 2019 ; Laustsen et al, 2015 ).…”
Section: The Overlap Between Snake and Human Activities Is Context-dependentmentioning
confidence: 99%
“…the widespread formation of blood clots consumes clotting factors and platelets) and extensive haemorrhage (Debono et al., 2017; Pla et al., 2017). Human fatalities following envenomation have been reported (Krüger & Lemke, 2019), although boomslang bites occur infrequently (Hamza et al., 2016; Wood, Sartorius, & Hift, 2016). As a diurnal and mainly arboreal snake, its diet consists primarily of arboreal lizards, in particular chameleons (Branch, 1998; Broadley, 1959) and fledgling birds to a varying extent (Covas, 2002; Smith, Layloo, Maritz, & Maritz, 2019).…”
Section: Introductionmentioning
confidence: 99%